BET 1: What is the incidence of cardiac arrhythmia in adult patients with acute infection prescribed fluoroquinolones?. Issue 10 (24th September 2019) - Chan, Kathryn; Fitzpatrick, Jada
Abstract : A shortcut review was carried out to establish the incidence of arrhythmia after prescription of a fluoroquinolone antibiotic. 332 papers were found using the reported searches, of which 14 presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. It is concluded that the incidence of arrhythmia after prescription of a fluoroquinolone antibiotic is low (<3%), but estimates are imprecise.